Temporohyoid osteoarthropathy in the horse. (14th January 2014) - Koch, C.; Witte, T.
Summary Temporohyoid osteoarthropathy (THO) is a well‐recognised clinical entity in horses. Temporohyoid osteoarthropathy is characterised by progressive osseous proliferation of the proximal portion of the stylohyoid and petrous temporal bones, and is generally described as a disease of middle‐aged horses. More recent reports also attribute a variety of clinical syndromes in young horses to THO, requiring a diversification of approaches to confirm the diagnosis and its significance, and to guide conservative and surgical treatment options. This commentary will review the purported aetiology, clinical syndromes, available diagnostic tests and treatment options of equine THO.